A practical guide for imparting the faith : comprehensive catechesis - Wilson, David J. (David Joseph), 1967- (Staten Island, N.Y. : Alba House, 2005)
"The goal of the book is to offer practical advice to those in parish ministry so that, by following the steps set forth in this process - from laying the foundation to putting the faith into practice by serving others - students will more easily assimilate and apply what is being taught to their various life situations. Each of its twelve chapters opens with a verse from Scripture that relates to the chapter's topic and purpose. Drawing heavily on the Church's documents and the teachings of the bishops following the Second Vatican Council, the book takes a theological concept and applies it to practical experience. Faith is a gift of God; nurturing it is our gift to Him. This book shows us how we can do that most effectively."--BOOK JACKET.
Prayer before reading this book -- Ch. 1. Contemporary Christian catechesis -- Ch. 2. Process versus content -- Ch. 3. Laying the foundation - building a community -- Ch. 4. The framework - evangelization -- Ch. 5. Raising the roof - catechesis -- Ch. 6. Turning on the electricity - prayer and worship -- Ch. 7. Working on the inside - justice and service -- Ch. 8. So what? -- Ch. 9. Seeing the results -- Ch. 10. The "X" factor - the catechist -- Ch. 11. The "Y" factor - the students and their questions -- Ch. 12. The alpha and the omega - to know, to love, to serve.
Keywords: Catechetics -- Catholic Church